A6.06 P120-Catenin is essential for fibroblast-like synoviocyte function in organising the synovial tissue. (24th February 2016) - Kartnig, F; Byrne, RA; Karonitsch, T; Calvo, I Olmos; Heinz, L; Bigenzahn, J; Niederreiter, B; Holinka, J; Steiner, G; Superti-Furga, G; Smolen, JS; Kiener, HP
Abstract : Background and objectives: Fibroblast like Synoviocytes (FLS) are key for the formation of the synovial lining / sublining architecture via unique cadherin-11 mediated cell-to-cell adherens junctions. Binding to the juxta-membrane domain of the cytoplasmic tail of cadherins, p120 is indispensable for the stabilisation of cadherins on the cell surface. By contrast, unbound p120-catenin interferes with small Rho GTPases, thereby regulating actin cytoskeletal organisation as well as NF-κB pathway activity. Here we probe into the function of p120-catenin for synovial tissue formation. Methods: Primary FLS were cultured from synovial tissue after synovectomy of RA classified patients. The knock down (KD) of p120-catenin was achieved by the expression of specific shRNA via a lentiviral vector. Immunoblotting was performed to verify decreased p120-catenin expression levels as well as the effects on the expression of cellular cadherin-11. 2D FLS cultures were analysed using phase contrast microscopy as well as confocal immunofluorescence imaging of actin filaments and cadherin-11 mediated cell-to-cell junctions. For the analysis of FLS capacity in forming synovial-like tissue, FLS were cultured in Matrigel® micromasses. Data quantification was done with ImageJ; for statistical analyses Graphpad Prism® was used. Results: p120-catenin silenced FLS demonstrated an altered cellular phenotype regarding the size, shape and the cytoskeletal organisation when compared to control cells. In conventional 2D cultures, the surface area covered by KD cells was increased threefold (p < 0.0001). Actin staining revealed pronounced stress fibres that were organised in parallel within the cell body. Further, polymerized actin was significantly elevated when compared to control cells, (p < 0.0001). Due to default p120-catenin, reduced quantities of cadherin-11 were observed by immunoblotting. This was consistent with decreased levels of cadherin-11 at cell-to-cell junctions as measured immunofluorescence signal intensity. Strikingly, loss of p120-catenin was associated with the impaired capacity of FLS to establish an organised synovial architecture. Conclusion: Although the immunological role of p120-catenin for FLS function in synovial inflammation (NF-kB activity) has yet to be shown, our findings strongly suggest the importance of p120-catenin for the formation of the normal synovial tissue.